Nutritional and nutraceutical potential of rice bean (Vigna umbellata) –a legume with hidden potential - Katoch, Rajan; Sanadya, Sanjay Kumar; Pathania, Kiran; Chaudhary, H. K. (Frontiers in Nutrition, 2023)
In the recent years there has been paradigm shift in global agriculture for the exploration of different underutilized crops as future potential crops. Rice bean [Vigna umbellata (Thunb.) Ohwi and Ohashi] one of the lesser known pulses among Vigna species has gained attention during last decade as food and nutritional security crop. Rice bean seeds are well-balanced source of beneficial constituents such as protein, carbohydrates, minerals, vitamins, polyunsaturated fatty acids (PUFAs) and anti-oxidants for health benefits and combating malnourishment in human. In the present investigation, seeds of 15 diverse rice bean accessions from north-western Himalayan region were analyzed for nutrients, anti-nutrients and nutraceutical traits. Significant differences were observed among genotypes for different traits. The rice bean genotypes revealed variation for major quality traits including total carbohydrates (50.56–56.87%), crude protein content (22.56–25.97%) and lipid content (1.87 to 3.17%) with the higher proportion of linolenic acid followed by linoleic acid which are nutritionally desirable PUFAs. The genotype IC-548758 revealed higher proportion of desirable quality traits. Among protein fractions, globulins and albumins constituted major seed storage protein fraction in rice bean seeds. The wide range variation was also observed for anti-nutrients like including raffinose family oligosaccharides (RFOs), phenolics, tannins, trypsin inhibitor (TI), phytic acid, lipoxygenase activity and saponin content among genotypes. Insignificant correlation among iron, zinc, magnesium and manganese revealed good selection accuracy for genetic biofortification program in rice bean. In summary, the genotype IC-548757, IC-548760 and IC-548770 revealed lower proportion of anti-nutrients, whereas, the genotype IC-548759 and IC-548757 revealed higher level of free radical scavenging activity indicating nutritional and nutraceutical superiority of these genotypes. Overall, the study revealed nutritional superiority of genotype IC-548770, IC-548758 and IC-548760 with balanced proportions of nutrients and anti-nutrients. Rice bean legume has the potential to support more sustainable and resilient food and nutritional security in future. Our study highlights the potential of different rice bean genotypes as functional ingredients for future food and nutritional security programmes.